Genetic diversity and population structure of selected lacustrine and riverine populations of African catfish, Clarias gariepinus (Burchell, 1822), in Kenya. (22nd February 2021) - Alal, George W.; Barasa, James E.; Chemoiwa, Emily J.; Kaunda‐Arara, Boaz; Akoll, Peter; Masembe, Charles
Abstract: Determining the genetic characteristics of natural fish stocks is useful for conservation and aquaculture programs. For African catfish, Clarias gariepinus, genetic characterization could help identify populations suitable as brood stock for culture, and those in need of conservation. This study determined the genetic diversity, population structure, and demographic history of C. gariepinus from Lakes Victoria (LV), Kenyatta (LKE), Kamnarok (LKA), and Rivers Nyando (NR), Tana (TR) and Sosiani (SR) in Kenya. Using 128 DNA sequences of D‐loop control region, 34 haplotypes were recovered, of which 79.4% were singletons. Only 7 haplotypes were shared between sites, implying little gene flow between sites. Number of haplotypes was highest in LKE and NR populations and lowest in SR. Haplotype diversity was highest in LV, and lowest in SR, while, nucleotide diversity was highest in LKA and lowest in LV. Phylogenetic analyses revealed five clusters: Lakes Victoria, Kamnarok and Kenyatta, and Rivers Tana and Nyando, from both maximum likelihood tree and minimum spanning network. This, together with significant F ST values among the sites imply population differentiation. Mismatch distributions were multi‐modal in LKA, LKE, NR and TR, signifying demographic equilibria. Neutrality tests Tajima`s D values for the sampled populations were negative and significantly different, suggesting stable populations. These results show the existence of genetically distinct populations of C. gariepinus that require spatially explicit management actions such as reducing fishing pressure, pollution, minimizing habitat destruction and fragmentation for sustainable utilisation of stocks.